Do age and comorbidity impair recovery during two years after treatment for endometrial cancer?. Issue 7 (September 2020) - van Walree, Inez C.; Hamaker, Marije E.; de Rooij, Belle H.; Boll, Dorry; van Huis-Tanja, Lieke H.; Emmelot-Vonk, Marielle H.; Ezendam, Nicole P.M.
Abstract: Background: A better understanding of the impact of age and comorbidity on health-related quality of life (HRQoL) may improve treatment decision-making in patients with endometrial cancer. We investigated whether either age or comorbidity is more strongly associated with changes in HRQoL over time. Methods: Endometrial cancer patients (n = 296) were invited to complete questionnaires after initial treatment and after 6, 12 and 24 months follow-up. Patients were divided into subgroups according to age (<60, 60–75 and ≥75 years) and according to comorbidity (0, 1, 2 or ≥3). HRQoL was measured with the five EORTC QLQ-C30 functioning scales. Linear mixed models were performed for the different subgroups to assess changes in HRQoL over time. HRQoL was also compared to longitudinal outcomes from an age- and gender-matched normative population. Results: The first questionnaire was returned by 221 patients (75%) of whom six were excluded due to progressive disease. Changes in HRQoL were mainly associated with cumulative comorbidity burden and not with age. Patients with comorbidity reported deterioration of physical and role functioning between 12 and 24 months. Compared to the normative population, patients initially scored higher on physical and role functioning, but at 24 months outcomes were no longer different. Conclusion: Cumulative comorbidity burden was more strongly associated with deterioration of HRQoL than patient's age. Therefore, patients with endometrial cancer and multiple comorbid conditions require careful follow-up of HRQoL after treatment.